The Singable Techniques are Used in Emma Heesters’s Translated Lyrics - Bahagia Saragih; Muhammad Natsir (Randwick International of Education and Linguistics Science Journal, 2023)
The aims of this study were to investigate the singability found in translated covered lyrics found in translated covered lyrics of “Melukis Senja”, “Maafkan Aku”, and “Cuek” by Emma Heesters. The study was conducted by using a content analysis research. The data of this study were taken from the lyrics of “Melukis Senja”, “Maafkan Aku”, and “Cuek”. The data of this study were the translated lyrics songs that appeared in “Melukis Senja”, “Maafkan Aku”, and “Cuek” songs. The data analysis was taken by observing, take notes, make a table the data based on the theory proposed by Franzon and Low. The findings indicated there are singable lyrics different from one of another. Based on the research results, the most frequently singable lyrics was the “Melukis Senja” song. There were even several singability served more than one purpose. Singability which served as an evaluation for the lyrics that has been translated by the translator.